Urgensi Transformasi Hukum Islam dalam Pemajuan Hak Asasi Manusia di Indonesia - Nasaruddin Umar (State Institute of Islamic Studies (IAIN) Palu, 2015)
The study is conducted in order to analyze the transformation of the values of Islamic law in both the anvil formation of legislation in Indonesia. This study is a descriptive normative legal-analysis using qualitative analysis techniques to primary legal materials and legal sekunder materials. The results of this study indicate that the values of Islamic law has been actualized in the legislation in the field of social protection in Indonesia. Transformation of the values of the Islamic Sharia through two approaches, namelythat are the substance of the principles of the laws and regulations, and actualization through matter of legislation.